Map of the Handbook of Meta-Research - Derrick, GE; Nuseibeh, N; Oancea, A; Xu, X (Edward Elgar Publishing, 2024)
This chapter introduces each contribution contained within the Handbook of Meta-Research. The chapters in the handbook are organised into four sections which represent many of the key focus areas of past and current meta-research. These four sections include: Public value of research; Policy and governance of research; Knowledge dynamics; and Research cultures and careers. The chapter ends by stating the main objective of this Handbook, which is to facilitate discussions within the meta-research space towards a more inclusive and interdisciplinary production of knowledge that we can use to simultaneously produce valuable, high-quality research as well as enrich the understanding of the environment in which we work.